Post-Disaster Mitigation: Material Assistance for Rehabilitation and Reconstruction by The East Java Provincial BPBD - Michael Imanuel Tarigan, (Jurnal Indonesia Sosial Sains, 2025)
Indonesia is a disaster-prone country due to its geographical location between the Asian and Australian continental plates, making it vulnerable to natural disasters such as tsunamis, landslides, and earthquakes. These disasters cause significant damage to infrastructure and residential areas, particularly in East Java, which ranks among the top 10 disaster-prone regions. This study aims to evaluate the post-disaster mitigation procedures for rehabilitation and reconstruction, focusing on the material assistance provided by the East Java Provincial Disaster Management Agency (BPBD). This qualitative study adopts a descriptive approach, utilizing both primary and secondary data sources. Primary data was collected through interviews with staff from the East Java BPBD, while secondary data was gathered from relevant documents and regulations. The study identifies that the East Java BPBD follows a structured procedure, with specific Standard Operating Procedures (SOPs) for providing material assistance and financial support for rehabilitation and reconstruction efforts. The process involves multiple stages of administrative checks, proposal evaluations, and field verifications. The findings reveal the effectiveness of these procedures in ensuring smooth coordination and timely distribution of assistance. The post-disaster rehabilitation and reconstruction procedures employed by the East Java BPBD are well-organized, with clear stages and SOPs in place. These procedures help streamline the administrative process and facilitate the efficient delivery of material assistance and funding. However, challenges in implementation may still arise, requiring continuous monitoring and refinement of the procedures.